2020
DOI: 10.1042/ns20190099
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs in neuropathic pain

Abstract: Neuro-immune alterations in the peripheral and central nervous system play a role in the pathophysiology of chronic pain in general, and members of the non-coding RNA (ncRNA) family, specifically the short, 22 nucleotide microRNAs (miRNAs) and the long non-coding RNAs (lncRNAs) act as master switches orchestrating both immune as well as neuronal processes. Several chronic disorders reveal unique ncRNA expression signatures, which recently generated big hopes for new perspectives for the development of diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 208 publications
0
34
0
Order By: Relevance
“…Whether the differential miRNAs and circRNAs were located within nerve endings, skin immune cells or extracellular space is unclear. Importantly, recent mounting literature has suggested that ncRNAs may act as 'master switches' in regulating the neuroimmune balance within the skin (183,184). Further investigation into ncRNA function may present exciting diagnostic and treatment applications for neuropathic pain states.…”
Section: Viral Disease-induced Neuropathymentioning
confidence: 99%
“…Whether the differential miRNAs and circRNAs were located within nerve endings, skin immune cells or extracellular space is unclear. Importantly, recent mounting literature has suggested that ncRNAs may act as 'master switches' in regulating the neuroimmune balance within the skin (183,184). Further investigation into ncRNA function may present exciting diagnostic and treatment applications for neuropathic pain states.…”
Section: Viral Disease-induced Neuropathymentioning
confidence: 99%
“…As master regulators of pain gene expression, miRNAs have emerged as critical pain modulators 14,15 . miR-544-3p is widely expressed in a variety of cell types and has been implicated in multiple physiological and pathological processes, such as cancer, stroke and cardiovascular disease 37,39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Primary sensory neurons with cell bodies in trigeminal ganglia or dorsal root ganglia (DRG) represent the primary origin of nociception, and are involved in both initiation and maintenance of pathological pain states 13 . Growing evidence suggests that miRNAs expressed in the DRG function as crucial pain modulators via the regulation of pain associated genes 14,15 . miRNA cluster miR-17-92 (including miR-17, miR-18, miR-19a, miR-19b and miR-92) were upregulated in the DRG in neuropathic pain models and in turn down-regulated potassium channels including Kcna1, Kcna4, Kcnc4, Kcnd3 and Kcnq5 16 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, many miRNAs have been reported in neurodegenerative diseases (22), cancer (23,24), bowel disease (25), and diabetic heart disease (DHD) (26). Although some lncRNAs (27,28) and miRNAs (29,30) have been reported in NP, there are still few reports on how lncRNAs, miRNAs and mRNAs jointly regulate the pathogenesis of NP. Zhou and colleagues (5) analyzed the expression pro le of non-coding RNAs in the spinal cord following spared nerve injury-induced NP by sequencing, and constructed lncRNA-miRNA-mRNA and circRNA-miRNA-mRNA networks in NP.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we constructed the lncRNA-mRNA-miRNA network in NP. The lncRNAs can be used as candidate indicators for NP (30). Various studies have provided new mechanisms for the molecular roles of miRNAs in the pathogenesis of NP (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%